Ovulation hormonal imbalance recognition system using saliva’s conductivity analysis based on potentiometric method - Romeo Jr. Jorda; Kit Erick Bartolome; Christopher Buban; Ma. Aimee De Los Reyes; Angelo Maingat; Micaela Joyce Oledan; Lean Karlo Tolentino (Institute of Advanced Engineering and Science, 2019)
Hormonal imbalance is often pointed out by medical experts to be the cause of menstrual irregularity, a common problem of women. This study aims to develop a device that would determine if a patient has hormonal imbalance by testing saliva’s conductivity onto the device for 28 consecutive days, thus, determining the cause of the patient’s menstrual irregularity. To test the accuracy of the device, the researchers selected three women residing in one home to use the device. To determine if a woman has hormonal imbalance, the data, when plotted in a chart, should have a sudden peak. However, data can’t be analyzed through visual assumptions only. Therefore, the data is analyzed through sample standard deviation. If one data is higher or lower than the sum and difference of the sample standard deviation and the mean, the woman is negative in hormonal imbalance. Comparing the result from the device and from the blood test, it is concluded that the results from the device matched the results from the blood test and medical expert interpretation.